2011
DOI: 10.1128/iai.00880-10
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus reuteri Ameliorates Disease Due to Enterohemorrhagic Escherichia coli in Germfree Mice

Abstract: Strains of enterohemorrhagic Escherichia coli (EHEC) are a group of Shiga toxin-producing food-borne pathogens that cause severe hemorrhagic colitis and can lead to hemolytic-uremic syndrome (HUS), a life-threatening condition that principally affects children and for which there is no effective treatment. We used a germfree mouse model of renal and enteric disease due to EHEC to determine if probiotic Lactobacillus reuteri ATCC PTA 6475 is effective in suppressing disease symptoms caused by EHEC. When germfre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…We observed that Helicobacter abundance increased in late summer/fall, when Lactobacillus levels are low. This might suggest that Lactobacillus confers protection against infection as has been demonstrated in laboratory mice ( Kabir et al, 1997 ; Pena et al, 2005 ; Medellin-Pena and Griffiths, 2009 ; Eaton et al, 2011 ). Alternatively, immune status (that is, IL-22 deficiency) has been linked to the abundance of Lactobacillus ( Zenewicz et al, 2013 ), potentially suggesting that these seasonal changes might be in part driven by the host response to bacterial infection.…”
Section: Discussionmentioning
confidence: 66%
“…We observed that Helicobacter abundance increased in late summer/fall, when Lactobacillus levels are low. This might suggest that Lactobacillus confers protection against infection as has been demonstrated in laboratory mice ( Kabir et al, 1997 ; Pena et al, 2005 ; Medellin-Pena and Griffiths, 2009 ; Eaton et al, 2011 ). Alternatively, immune status (that is, IL-22 deficiency) has been linked to the abundance of Lactobacillus ( Zenewicz et al, 2013 ), potentially suggesting that these seasonal changes might be in part driven by the host response to bacterial infection.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the genes cyclopropane fatty acid synthase (cfa) [43] and L. reuteri-specific immunoregulatory (rsiR) gene [44] have been implicated in the anti-inflammatory properties of L. reuteri 6475. In addition to these immunomodulatory properties in vitro, L. reuteri 6475 has also shown promising effects in animal studies [45][46][47].…”
Section: Immunomodulatory Effects Of Selected Lactic Acid Bacteriamentioning
confidence: 96%
“…At the gastrointestinal mucosal surface, the presence of lactobacilli is associated with downregulation of immune response to inflammatory stimuli, 20,21 but a similar process has not been defined in the genital tract. Because most of the adverse health outcomes associated with BV are presumably related to inflammatory complications of BV, understanding whether the presence of (or introduction of) Lactobacillus species could mitigate those complications is important.…”
Section: What Is a Healthy Vagina?mentioning
confidence: 99%